Resin composition and method for producing connection structure

The resin composition with a thermosetting component, flux, and solder particles addresses the misalignment issue in laser transfer methods by improving the capture and alignment of high-speed semiconductor chips, ensuring precise and effective connections.

JP7617347B1Active Publication Date: 2025-01-17SEKISUI CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024566008
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-06-24
Publication Date
2025-01-17
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

The challenge in the laser transfer method for arranging semiconductor chips is the accurate placement of high-speed flying chips, which often results in misalignment and ineffective conductive connections due to the impact upon landing on the circuit board.

Method used

A resin composition comprising a thermosetting component, flux, a thixotropic agent, and solder particles is used to capture and accurately place semiconductor chips during the laser transfer method, enhancing the ability to align and connect electrodes effectively.

Benefits of technology

The resin composition improves the capture and alignment of high-speed semiconductor chips, ensuring precise placement and effective conductive connections by reducing misalignment and enhancing solder cohesiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617347000004
    Figure 0007617347000004
  • Figure 0007617347000005
    Figure 0007617347000005
  • Figure 0007617347000006
    Figure 0007617347000006
Patent Text Reader

Abstract

A resin composition (11) capable of enhancing the ability to capture semiconductor chips (3) flying at high speed is provided. The resin composition (11) according to the present invention contains a thermosetting component (11B), a flux (11C), a thixotropic agent that is liquid at 25° C., and solder particles (11A).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing solder particles. The present invention also relates to a method for producing a connection structure using the resin composition. [Background technology]

[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known. In the anisotropic conductive materials, conductive particles are dispersed in a binder. Solder particles are widely used as the conductive particles.

[0003] The anisotropic conductive material is used to obtain various connection structures. Examples of connections using the anisotropic conductive material include connections between a flexible printed circuit board and a glass substrate (FOG (film on glass)), between a semiconductor chip and a flexible printed circuit board (COF (chip on film)), between a semiconductor chip and a glass substrate (COG (chip on glass)), and between a flexible printed circuit board and a glass epoxy substrate (FOB (film on board)).

[0004] In recent years, devices using connection structures have become smaller and lighter. Accordingly, there is a demand for the development of connection structures using fine semiconductor chips such as micro-LED (micro-light emitting diode) chips. Laser transfer methods have attracted attention as a method for placing fine semiconductor chips such as micro-LED chips on circuit boards.

[0005] The following Patent Document 1 discloses a laser transfer device. In this laser transfer device, an original substrate on which multiple elements are formed is placed above a destination substrate. By irradiating the original substrate with laser light from above, multiple transfer target elements, which are the transfer targets among the multiple elements, are moved downward, and the transfer target elements are transferred to the destination substrate.

[0006] The following Patent Document 2 discloses a transfer method for transferring a chip component held on a transfer substrate via a photocurable adhesive layer to a destination substrate. The transfer method includes an exposure step of exposing the adhesive layer to light having a wavelength that hardens the adhesive layer in a pattern to partially reduce the adhesive strength of the adhesive layer, and a laser lift-off step of transferring the chip component to the destination substrate by a laser lift-off method after the exposure step. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] WO2020 / 188780A1 [Patent Document 2] JP 2020-53558 A Summary of the Invention [Problem to be solved by the invention]

[0008] In the method of arranging semiconductor chips using laser transfer, multiple semiconductor chips can be moved and mounted in one go from a wafer substrate (source substrate) to a circuit substrate (destination substrate), thereby increasing the productivity of the connection structure.

[0009] However, in the method of placing a semiconductor chip using the laser transfer method, the semiconductor chip may not be placed accurately in a predetermined place on the circuit board (connection target member) due to the impact when the semiconductor chip, which comes flying at high speed, hits the circuit board (connection target member). If misalignment occurs during placement of the semiconductor chip, it may not be possible to electrically connect the upper and lower electrodes.

[0010] An object of the present invention is to provide a resin composition capable of enhancing the capturing ability of a semiconductor chip flying at high speed. Another object of the present invention is to provide a method for producing a connection structure using the resin composition. [Means for solving the problem]

[0011] As a result of extensive research, the inventors have discovered that by placing a specific resin composition on the surface of a circuit board (a component to be connected), it is possible to effectively capture a semiconductor chip flying at high speed by a laser transfer method or the like.

[0012] Disclosed herein is the following resin composition and a method for producing a connection structure using the resin composition.

[0013] Item 1. A resin composition comprising a thermosetting component, a flux, a thixotropic agent that is liquid at 25°C, and solder particles.

[0014] Item 2. The resin composition according to item 1, wherein the flux includes a first flux having an even number of carbon atoms in a main chain and a second flux having an odd number of carbon atoms in a main chain.

[0015] Item 3. The hydrogen bond term δH in the Hansen solubility parameter of the thixotropic agent is 10 MPa 1 / 2 Item 3. The resin composition according to item 2, wherein the number of carbon atoms in the main chain of the first flux is an even number of 4 or more and 14 or less, and the number of carbon atoms in the main chain of the second flux is an odd number of 3 or more and 11 or less.

[0016] Item 4. The resin composition according to item 2 or 3, wherein the first flux has an average particle size of 10 μm or less.

[0017] Item 5. The resin composition according to any one of Items 2 to 4, wherein the second flux is soluble in the thixotropic agent at 25° C.

[0018] Item 6. The resin composition according to any one of Items 2 to 5, wherein the content of the second flux is 1% by weight or more and 20% by weight or less in 100% by weight of the resin composition.

[0019] Item 7. The resin composition according to any one of Items 1 to 6, wherein the thixotropic agent contains glycerin.

[0020] Item 8. The resin composition according to any one of Items 1 to 7, wherein the content of the flux is 5% by weight or more and 25% by weight or less in 100% by weight of the resin composition.

[0021] Item 9. The resin composition according to any one of Items 1 to 8, wherein the solder particles have an average particle size of 10 μm or less.

[0022] Item 10. A method for producing a connection structure, comprising: a first arrangement step of arranging the resin composition on a surface of a first connection target member having at least one first electrode on a surface thereof, the resin composition being used; a second arrangement step of moving a second connection target member having at least one second electrode on a surface opposite to the first connection target member side of the resin composition by a laser transfer method, and arranging the second connection target member so that the first electrode and the second electrode face each other; and a connection step of forming a connection portion connecting the first connection target member and the second connection target member using the resin composition by heating the resin composition to a temperature equal to or higher than the melting point of the solder particles, and electrically connecting the first electrode and the second electrode with a solder portion in the connection portion.

[0023] Item 11. The method for producing a connection structure according to Item 10, wherein in the second arrangement step, the second connection target member is moved by a laser transfer method at a speed of 1 cm / s or more on a surface of the resin composition opposite the first connection target member side, and the second connection target member is arranged so that the first electrode and the second electrode face each other. Effect of the Invention

[0024] The resin composition according to the present invention contains a thermosetting component, a flux, a thixotropic agent that is liquid at 25° C., and solder particles. Since the resin composition according to the present invention has the above-mentioned configuration, it can enhance the capture of semiconductor chips flying at high speed. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a cross-sectional view that typically shows a connection structure obtained by using a resin composition according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating the steps of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view illustrating steps of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view illustrating steps of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing a modified example of the connection structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention will be described in detail below.

[0027] (Resin composition) The resin composition according to the present invention contains a thermosetting component, a flux, a thixotropic agent that is liquid at 25° C., and solder particles.

[0028] Conventionally, in the method of placing semiconductor chips using the laser transfer method, the semiconductor chip may not be placed accurately in a predetermined place on the circuit board (connection target member) due to the impact when the semiconductor chip, which comes flying at high speed, hits the circuit board (connection target member). If misalignment occurs during placement of the semiconductor chip, it may not be possible to electrically connect the upper and lower electrodes.

[0029] Since the resin composition according to the present invention has the above-mentioned configuration, it is possible to enhance the capture of semiconductor chips arriving at high speed. In particular, it is possible to enhance the capture of semiconductor chips arriving at high speed by the laser transfer method. As a result, it is possible to accurately place the arriving semiconductor chip at a predetermined location on the circuit board (connection target member) (effectively suppressing misalignment during placement of the semiconductor chip).

[0030] In the present invention, the use of a specific resin composition greatly contributes to obtaining the above-mentioned effects.

[0031] The resin composition is disposed on the surface of a connection target member (circuit board, transfer destination substrate) and used in a method for producing a connection structure. The resin composition is suitably used in a method for producing a connection structure to effectively capture a semiconductor chip flying at high speed by a laser transfer method. The resin composition is preferably a resin composition for capturing a semiconductor chip by a laser transfer method.

[0032] In particular, the resin composition according to the present invention is preferably used for connecting semiconductor chips by a laser transfer method (use of the resin composition for connecting semiconductor chips by a laser transfer method). More specifically, the resin composition according to the present invention is more preferably used for connecting semiconductor chips to a substrate by a laser transfer method (use of the resin composition for connecting semiconductor chips to a substrate by a laser transfer method).

[0033] The contact angle of the resin composition with water at 25°C is preferably 65° or less, more preferably 60° or less, even more preferably 55° or less, and particularly preferably 45° or less. When the contact angle of the resin composition with water at 25°C is the above upper limit or less, the capture ability of the semiconductor chip flying at high speed by the laser transfer method can be further improved. Specifically, the electrodes of the semiconductor chip generally contain gold, copper, or an alloy thereof, and therefore the surface of the electrode of the semiconductor chip is often hydrophilic. When the contact angle of the resin composition with water at 25°C according to the present invention is the above upper limit or less, the surface of the resin composition has hydrophilicity, so that the affinity with the surface of the electrode of the semiconductor chip is high, and when the resin composition is placed on the surface of the connection target member (circuit board), the capture ability of the semiconductor chip flying at high speed by the laser transfer method can be further improved. The lower limit of the contact angle of the resin composition with water at 25°C is not particularly limited. The contact angle of the resin composition with water at 25°C may be 0° or more, may exceed 0°, may be 1° or more, or may be 5° or more. The range of the contact angle can be set by appropriately selecting the lower limit and the upper limit.

[0034] The contact angle of the resin composition with water at 25°C can be measured, for example, by the following method. 1 ml of water is dropped onto the surface of the resin composition, and the contact angle of the resin composition with water is measured using a contact angle measuring device. An example of the contact angle measuring device is "DMo-601" manufactured by KYOWA. The contact angle of the resin composition with water at 25°C is measured 10 seconds after the water is placed on the surface of the resin composition.

[0035] The contact angle of the resin composition with water at 25°C can be adjusted by the following methods, etc.: A method of combining a plurality of skeletons of a thermosetting component such as an epoxy resin; A method of selecting a skeleton of a thermosetting component such as an epoxy resin; A method of selecting a side chain of a thermosetting component such as an epoxy resin; A method of dispersing an additive that is liquid at 25°C in the resin composition.

[0036] The resin composition is preferably in a liquid state at 25°C. A paste state is included in the liquid state. The resin composition is preferably in a paste state at 25°C. The resin composition contains solder particles, and is therefore a conductive material. The resin composition is preferably a conductive paste. The resin composition is preferably a conductive paste at 25°C. In these cases, the resin composition can be applied more thinly and satisfactorily on the surface of the connection target member, the capture of semiconductor chips flying at high speed by the laser transfer method can be more effectively enhanced, and the cohesiveness of the solder during conductive connection can be more effectively enhanced.

[0037] The viscosity (η25) of the resin composition at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 250 Pa·s or less, more preferably 200 Pa·s or less. When the viscosity (η25) is equal to or greater than the lower limit, the capturing ability of semiconductor chips flying at high speed by the laser transfer method can be more effectively improved. When the viscosity (η25) is equal to or less than the upper limit, the resin composition can be applied thinly and satisfactorily on the surface of the connection target member, and the cohesiveness of the solder during conductive connection can be effectively improved. The viscosity (η25) can be appropriately adjusted by the types and amounts of the blended components.

[0038] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE-22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.

[0039] The viscosity (ηmp) of the resin composition at the melting point of the solder particles is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, and preferably 10 Pa·s or less, more preferably 5 Pa·s or less. The viscosity (ηmp) can be appropriately adjusted depending on the type and amount of the blended components. When the viscosity (ηmp) is equal to or more than the lower limit and equal to or less than the upper limit, the cohesiveness of the solder during conductive connection can be more effectively increased, voids at the connection portion can be more effectively suppressed, and the overflow of the resin composition to areas other than the connection portion can be more effectively suppressed. When the viscosity (ηmp) is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between electrodes can be more effectively increased, and the conduction reliability between electrodes can be more effectively increased.

[0040] The viscosity (ηmp) can be measured, for example, using a viscoelasticity measuring device ("HAAKE" manufactured by SCIENTIFIC Corporation) under conditions of stress control of 1 Pa, frequency of 1 Hz, heating rate of 20°C / min, and measurement temperature range of 25°C to 200°C. However, if the melting point of the solder particles exceeds 200°C, the upper temperature limit is set to the melting point of the solder particles. In this measurement, the viscosity (ηmp) is calculated by reading the viscosity at the melting point of the solder particles.

[0041] The resin composition can be used as a conductive paste, a conductive film, and the like. The conductive paste is preferably an anisotropic conductive paste, and the conductive film is preferably an anisotropic conductive film. From the viewpoint of more effectively suppressing positional deviation during arrangement of the connection target components and more effectively enhancing the cohesiveness of the solder during conductive connection, the resin composition is preferably in the form of a paste, and is preferably a conductive paste. The resin composition is suitably used for electrical connection of electrodes. The resin composition is preferably a circuit connection material.

[0042] Each component contained in the resin composition will be described below. In this specification, the term "(meth)acrylate" refers to acrylate and methacrylate. The term "(meth)acrylic" refers to acrylic and methacrylic. The term "(meth)acryloyl" refers to acryloyl and methacryloyl.

[0043] (thermosetting component) The resin composition according to the present invention includes a thermosetting component. The thermosetting component preferably includes a thermosetting compound. The resin composition may or may not include a thermosetting agent as a thermosetting component. Since the resin composition according to the present invention has the above configuration, even if the resin composition does not include a thermosetting agent, it can enhance the capture of a semiconductor chip flying at high speed by a laser transfer method. From the viewpoint of more effectively enhancing the cohesiveness of the solder during conductive connection, it is preferable that the resin composition does not include a thermosetting agent. In order to cure the resin composition more satisfactorily, the resin composition may include a curing accelerator as a thermosetting component.

[0044] (Thermosetting component: thermosetting compound) The resin composition according to the present invention preferably contains a thermosetting compound. The thermosetting compound is a compound that can be cured by heating. The thermosetting compound is not particularly limited. Examples of the thermosetting compound include oxetane compounds, epoxy compounds, episulfide compounds, (meth)acrylic compounds, phenolic compounds, amino compounds, unsaturated polyester compounds, polyurethane compounds, silicone compounds, and polyimide compounds. From the viewpoint of further improving the curability and viscosity of the resin composition and further increasing the conduction reliability, the thermosetting compound is preferably an epoxy compound or an episulfide compound, and more preferably an epoxy compound. The resin composition preferably contains an epoxy compound or an episulfide compound, and more preferably contains an epoxy compound. The thermosetting compound may be used alone or in combination of two or more.

[0045] The epoxy compound is a compound having at least one epoxy group. Examples of the epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, phenol novolac type epoxy compounds, biphenyl type epoxy compounds, biphenyl novolac type epoxy compounds, biphenol type epoxy compounds, naphthalene type epoxy compounds, fluorene type epoxy compounds, phenol aralkyl type epoxy compounds, naphthol aralkyl type epoxy compounds, dicyclopentadiene type epoxy compounds, anthracene type epoxy compounds, epoxy compounds having an adamantane skeleton, epoxy compounds having a tricyclodecane skeleton, naphthylene ether type epoxy compounds, and epoxy compounds having a triazine nucleus in the skeleton. The epoxy compounds may be used alone or in combination of two or more.

[0046] The epoxy compound is liquid or solid at room temperature (25°C), and when the epoxy compound is solid at room temperature, the melting temperature of the epoxy compound is preferably equal to or lower than the melting point of the solder particles. By using the preferred epoxy compound, the viscosity is high at the stage of bonding the connection target components, and when acceleration is applied due to impact during transportation, etc., the positional deviation between the connection target components (circuit board) and the semiconductor chip can be suppressed. Furthermore, the viscosity of the resin composition can be greatly reduced by the heat during curing, and the aggregation of the solder during conductive connection can be efficiently promoted.

[0047] From the viewpoint of more effectively increasing insulation reliability and more effectively increasing conduction reliability, it is preferable that the thermosetting component contains an epoxy compound, and it is preferable that the thermosetting compound contains an epoxy compound.

[0048] From the viewpoint of disposing the solder on the electrodes more effectively, the thermosetting compound preferably contains a thermosetting compound having a polyether skeleton.

[0049] Examples of the thermosetting compound having a polyether skeleton include a compound having a glycidyl ether group at both ends of an alkyl chain having 3 to 12 carbon atoms, and a polyether-type epoxy compound having a polyether skeleton having 2 to 4 carbon atoms and a structural unit in which 2 to 10 polyether skeletons are bonded consecutively.

[0050] From the viewpoint of more effectively increasing the heat resistance of the cured product, the thermosetting compound preferably includes a thermosetting compound having an isocyanuric skeleton.

[0051] Examples of the thermosetting compound having an isocyanuric skeleton include triisocyanurate type epoxy compounds, such as the TEPIC series manufactured by Nissan Chemical Industries, Ltd. (TEPIC-G, TEPIC-S, TEPIC-SS, TEPIC-HP, TEPIC-L, TEPIC-PAS, TEPIC-VL, and TEPIC-UC).

[0052] From the viewpoints of more efficiently disposing the solder on the electrodes, more effectively increasing the reliability of conduction between the upper and lower electrodes to be connected, and more effectively suppressing discoloration of the thermosetting compound, it is preferable that the thermosetting compound has high heat resistance, and more preferably contains a novolac type epoxy compound. Novolac type epoxy compounds have relatively high heat resistance.

[0053] In 100% by weight of the resin composition, the content of the thermosetting compound is preferably 5% by weight or more, more preferably 8% by weight or more, even more preferably 10% by weight or more, and preferably 99% by weight or less, more preferably 90% by weight or less, even more preferably 80% by weight or less, and particularly preferably 70% by weight or less. When the content of the thermosetting compound is equal to or more than the lower limit and equal to or less than the upper limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be more effectively improved, the solder can be more efficiently arranged on the electrodes, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. From the viewpoint of more effectively improving the impact resistance of the resulting connection structure, the content of the thermosetting compound is preferably large.

[0054] In 100% by weight of the resin composition, the content of the epoxy compound is preferably 5% by weight or more, more preferably 8% by weight or more, even more preferably 10% by weight or more, and preferably 99% by weight or less, more preferably 90% by weight or less, even more preferably 80% by weight or less, and particularly preferably 70% by weight or less. When the content of the epoxy compound is above the lower limit and below the upper limit, the capture of the semiconductor chip flying at high speed by the laser transfer method can be more effectively improved, the solder can be more efficiently arranged on the electrodes, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. From the viewpoint of further improving the impact resistance of the resulting connection structure, the content of the epoxy compound is preferably high.

[0055] In 100% by weight of the resin composition, the content of the novolac type epoxy compound is preferably 1% by weight or more, more preferably 3% by weight or more, even more preferably 5% by weight or more, and preferably 99% by weight or less, more preferably 90% by weight or less, even more preferably 80% by weight or less, and particularly preferably 70% by weight or less. When the content of the novolac type epoxy compound is above the lower limit and below the upper limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be more effectively improved, the solder can be more efficiently arranged on the electrodes, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. From the viewpoint of further improving the impact resistance of the resulting connection structure, the content of the novolac type epoxy compound is preferably high.

[0056] (Flux) The resin composition contains a flux, which can more effectively increase the cohesion of the solder during conductive connection.

[0057] Examples of the flux include zinc chloride, a mixture of zinc chloride and an inorganic halide, a mixture of zinc chloride and an inorganic acid, a molten salt, phosphoric acid, a derivative of phosphoric acid, an organic acid, an organic acid amine salt, an organic halide, hydrazine, an amine compound different from the organic acid amine salt, and rosin, etc. Only one type of the flux may be used, or two or more types may be used in combination.

[0058] The flux preferably contains an organic acid or an organic acid amine salt. The organic acid is preferably a dicarboxylic acid, and the organic acid amine salt is preferably a dicarboxylic acid amine salt. The flux preferably contains a dicarboxylic acid or a dicarboxylic acid amine salt, and more preferably contains a dicarboxylic acid and a dicarboxylic acid amine salt.

[0059] The dicarboxylic acids include glutaric acid, adipic acid, azelaic acid, and pimelic acid.

[0060] Examples of the dicarboxylate amine salt include benzylamine glutaric acid salt, benzylamine adipate salt, benzylamine azelaic acid salt, stearylamine glutaric acid salt, stearylamine adipate salt, and stearylamine azelaic acid salt.

[0061] The flux is preferably a solid. The flux may be spherical or may have a shape other than spherical, or may be flat.

[0062] From the viewpoint of more effectively increasing the capture of semiconductor chips flying at high speed by the laser transfer method, the flux preferably includes two or more types of fluxes having different carbon numbers in the main chain. From the viewpoint of more effectively increasing the capture of semiconductor chips flying at high speed by the laser transfer method, the flux preferably includes a first flux having an even carbon number in the main chain and a second flux having an odd carbon number in the main chain. As the first flux, only one type of flux may be used, or two or more types of flux may be used. As the second flux, only one type of flux may be used, or two or more types of flux may be used.

[0063] The number of carbon atoms in the main chain of the first flux is an even number. The number of carbon atoms in the main chain of the first flux is an even number, and the number of carbon atoms in the main chain of the first flux is preferably 4 or more, more preferably 6 or more, and preferably 14 or less, more preferably 12 or less, even more preferably 10 or less, and particularly preferably 8 or less. The number of carbon atoms in the main chain of the first flux is preferably an even number of 4 or more and 14 or less. When the number of carbon atoms in the main chain of the first flux is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be arranged on the electrode more efficiently.

[0064] The number of carbon atoms in the main chain of the second flux is an odd number. The number of carbon atoms in the main chain of the second flux is an odd number, and the number of carbon atoms in the main chain of the second flux is preferably 3 or more, and preferably 11 or less, more preferably 9 or less, and further preferably 7 or less. The number of carbon atoms in the main chain of the second flux is preferably an odd number of 3 or more and 11 or less. When the number of carbon atoms in the main chain of the second flux is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be arranged on the electrode more efficiently.

[0065] The average particle diameter of the flux (average particle diameter of the entire flux) is preferably 10 μm or less, more preferably 7 μm or less, even more preferably 5 μm or less, and particularly preferably 3 μm or less. When the average particle diameter of the flux is equal to or less than the upper limit, the capturing ability of semiconductor chips flying at high speed by the laser transfer method can be more effectively improved. The lower limit of the average particle diameter of the flux is not particularly limited. The average particle diameter of the flux may be 0.01 μm or more, 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more. The range of the average particle diameter of the flux can be set by appropriately selecting the lower limit value and the upper limit value.

[0066] The average particle diameter of the first flux is preferably 10 μm or less, more preferably 7 μm or less, and even more preferably 5 μm or less. When the average particle diameter of the first flux is equal to or less than the upper limit, the capturing ability of semiconductor chips flying at high speed by the laser transfer method can be more effectively improved. The lower limit of the average particle diameter of the first flux is not particularly limited. The average particle diameter of the first flux may be 0.5 μm or more, or 1.0 μm or more. The range of the average particle diameter of the first flux can be set by appropriately selecting the lower limit value and the upper limit value.

[0067] The average particle diameter of the second flux is preferably 7 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. When the average particle diameter of the second flux is equal to or less than the upper limit, the capturing ability of semiconductor chips flying at high speed by the laser transfer method can be more effectively improved. The lower limit of the average particle diameter of the second flux is not particularly limited. The average particle diameter of the second flux may be 0.01 μm or more, or may be 0.1 μm or more. The range of the average particle diameter of the second flux can be set by appropriately selecting the lower limit value and the upper limit value.

[0068] The average particle diameter of the flux and the average particle diameters of the first and second fluxes are number average particle diameters. The average particle diameter of the flux and the average particle diameters of the first and second fluxes are obtained, for example, by observing 50 arbitrary fluxes with an electron microscope or an optical microscope and calculating the average particle diameter of each flux, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each flux is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary fluxes with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the laser diffraction particle size distribution measurement, the particle diameter of each flux is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the flux and the average particle diameters of the first and second fluxes are preferably calculated by laser diffraction particle size distribution measurement.

[0069] The flux and the first and second fluxes may be pulverized products of commercially available fluxes. Examples of methods for pulverizing commercially available fluxes include agate pulverization, jet mill pulverization, and bead mill pulverization.

[0070] The coefficient of variation (CV value) of the particle diameter of the flux (coefficient of variation (CV value) of the particle diameter of the entire flux) is preferably 10% or less, more preferably 5% or less. When the coefficient of variation of the particle diameter of the flux is equal to or less than the upper limit, the flux can be arranged on the electrode more efficiently. The lower limit of the coefficient of variation (CV value) of the particle diameter of the flux is not particularly limited. The coefficient of variation (CV value) of the particle diameter of the flux may be 0% or more, 1% or more, or 5% or more. The range of the coefficient of variation of the particle diameter of the flux can be set by appropriately selecting the lower limit and the upper limit.

[0071] The coefficient of variation (CV value) of the particle size of the flux can be measured as follows.

[0072] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of particle size of flux Dn: Average particle size of flux

[0073] The activation temperature (melting point) of the flux is preferably 50° C. or higher, more preferably 70° C. or higher, and even more preferably 80° C. or higher, and is preferably 200° C. or lower, more preferably 190° C. or lower, and even more preferably 180° C. or lower. When the activation temperature of the flux is equal to or higher than the lower limit and equal to or lower than the upper limit, the flux effect is more effectively exerted, and the solder is more efficiently arranged on the electrode. The activation temperature (melting point) of the flux is preferably 70° C. or higher and 190° C. or lower, and particularly preferably 80° C. or higher and 180° C. or lower.

[0074] The activation temperature (melting point) of the flux can be determined by differential scanning calorimetry (DSC). An example of a DSC device is "EXSTAR DSC7020" manufactured by SII Corporation.

[0075] Examples of the flux having an active temperature (melting point) of 80° C. or higher and 180° C. or lower include dicarboxylic acids such as glutaric acid (melting point 96° C.), glutaric acid benzylamine salt (melting point 108° C.), adipic acid (melting point 152° C.), adipic acid benzylamine salt (melting point 180° C.), pimelic acid (melting point 104° C.), and suberic acid (melting point 142° C.), benzoic acid (melting point 122° C.), and malic acid (melting point 130° C.).

[0076] The flux preferably has a boiling point of 200° C. or lower.

[0077] From the viewpoint of improving the coatability and screen printability of the resin composition, the second flux is preferably soluble in the thixotropic agent at 25°C. The first flux may or may not be soluble in the thixotropic agent at 25°C. From the viewpoint of improving the coatability and screen printability of the resin composition and enhancing the cohesiveness of the solder particles, it is preferable that the first flux is not soluble in the thixotropic agent at 25°C, and the second flux is soluble in the thixotropic agent at 25°C. In this specification, "the flux is soluble in the thixotropic agent" means that when 10 g of the flux is placed in 20 g of the thixotropic agent and held at 25°C for 10 minutes, the weight of the flux that dissolves in the thixotropic agent is 4 g or more.

[0078] The flux and the first and second fluxes may be dispersed in a resin composition or may be attached to the surface of a solder particle. The second flux may be dissolved in a thixotropic agent before use. The material of the resin composition may include the second flux dissolved in a thixotropic agent.

[0079] From the viewpoint of disposing the solder on the electrode more efficiently, the first flux is preferably 1,10-decanedicarboxylic acid, adipic acid, or a salt thereof, and more preferably adipic acid or a salt of adipic acid. From the viewpoint of disposing the solder on the electrode more efficiently, the first flux is preferably 1,10-decanedicarboxylic acid or adipic acid, and more preferably adipic acid.

[0080] From the viewpoint of disposing the solder on the electrode more efficiently, the second flux is preferably pimelic acid, azelaic acid, glutaric acid or a salt thereof, more preferably azelaic acid, a salt of azelaic acid, glutaric acid or a salt of glutaric acid. From the viewpoint of disposing the solder on the electrode more efficiently, the second flux is preferably pimelic acid, glutaric acid or a salt thereof, more preferably glutaric acid or a salt of glutaric acid. From the viewpoint of disposing the solder on the electrode more efficiently, the second flux is preferably pimelic acid or glutaric acid, more preferably glutaric acid.

[0081] The flux is preferably a flux that releases cations when heated. The first flux is preferably a flux that releases cations when heated. The second flux is preferably a flux that releases cations when heated. By using a flux that releases cations when heated, the solder can be more efficiently placed on the electrodes.

[0082] In 100% by weight of the resin composition, the content of the flux (content of the entire flux) is preferably 5% by weight or more, preferably 10% by weight or more, more preferably 15% by weight or more, and preferably 30% by weight or less, more preferably 25% by weight or less. When the content of the flux is equal to or more than the lower limit and equal to or less than the upper limit, the oxide film is more unlikely to be formed on the surfaces of the solder and the electrodes, and the oxide film formed on the surfaces of the solder and the electrodes can be more effectively removed. When the flux includes the first flux and the second flux, the content of the flux indicates the sum of the content of the first flux and the content of the second flux (hereinafter the same).

[0083] In 100% by weight of the resin composition, the content of the first flux is preferably 5% by weight or more, more preferably 8% by weight or more, and even more preferably 10% by weight or more, and is preferably 25% by weight or less, more preferably 20% by weight or less, and even more preferably 15% by weight or less. When the content of the first flux is equal to or more than the lower limit and equal to or less than the upper limit, the solder cohesion can be improved.

[0084] In 100% by weight of the resin composition, the content of the second flux is preferably 1% by weight or more, more preferably 2% by weight or more, and even more preferably 5% by weight or more, and is preferably 25% by weight or less, more preferably 20% by weight or less, and even more preferably 15% by weight or less. When the content of the second flux is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0085] In 100% by weight of the flux, the content of the first flux is preferably 40% by weight or more, more preferably 50% by weight or more, even more preferably 60% by weight or more, and is preferably 100% by weight or less, more preferably less than 100% by weight, even more preferably 90% by weight or less, particularly preferably 80% by weight or less, and most preferably 70% by weight or less. When the content of the first flux is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0086] The content of the flux (total content of the flux) relative to 100 parts by weight of the thixotropic agent is preferably 100 parts by weight or more, more preferably 150 parts by weight or more, even more preferably 200 parts by weight or more, and is preferably 500 parts by weight or less, more preferably 400 parts by weight or less, and even more preferably 300 parts by weight or less. When the content of the flux is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0087] The content of the first flux relative to 100 parts by weight of the thixotropic agent is preferably 10 parts by weight or more, more preferably 20 parts by weight or more, even more preferably 40 parts by weight or more, even more preferably 100 parts by weight or more, particularly preferably 150 parts by weight or more, most preferably 200 parts by weight or more, and preferably 500 parts by weight or less, more preferably 400 parts by weight or less, and even more preferably 300 parts by weight or less. When the content of the first flux is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0088] The content of the second flux is preferably 10 parts by weight or more, more preferably 20 parts by weight or more, and even more preferably 40 parts by weight or more, and is preferably 100 parts by weight or less, more preferably 80 parts by weight or less, and even more preferably 60 parts by weight or less, relative to 100 parts by weight of the thixotropic agent. When the content of the second flux is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0089] (thixotropic agent) The resin composition contains a thixotropic agent that is liquid at 25°C.

[0090] Examples of the thixotropic agent include ethylene glycol, diethylene glycol, 2-phenylethanol, 1,3-propanediol, glycerin, etc. The thixotropic agent may be used alone or in combination of two or more kinds.

[0091] From the viewpoint of improving the coatability and screen printability, the thixotropic agent preferably contains a compound having polarity, and more preferably contains a compound having a hydroxyl group or a carboxyl group. From the viewpoint of improving the coatability and screen printability, the thixotropic agent preferably contains ethylene glycol, diethylene glycol, 2-phenylethanol, 1,3-propanediol, or glycerin, and more preferably contains ethylene glycol, 1,3-propanediol, or glycerin. From the viewpoint of improving the coatability and screen printability, the thixotropic agent particularly preferably contains glycerin.

[0092] From the viewpoint of improving the coatability and screen printability of the resin composition, it is preferable that the second flux contains azelaic acid, a salt of azelaic acid, glutaric acid or a salt of glutaric acid, and the thixotropic agent contains glycerin or 1,3-propanediol. From the viewpoint of improving the coatability and screen printability of the resin composition, it is preferable that the second flux is azelaic acid, a salt of azelaic acid, glutaric acid or a salt of glutaric acid, and the thixotropic agent is glycerin or 1,3-propanediol. From the viewpoint of improving the coatability and screen printability of the resin composition, it is preferable that the second flux contains glutaric acid or a salt of glutaric acid, and the thixotropic agent contains glycerin. From the viewpoint of improving the coatability and screen printability of the resin composition, it is preferable that the second flux is glutaric acid or a salt of glutaric acid, and the thixotropic agent is glycerin. From the viewpoint of improving the coatability and screen printability of the resin composition, it is preferable that the second flux is glutaric acid and the thixotropic agent is glycerin.

[0093] From the viewpoint of improving the coatability and screen printability of the resin composition, it is particularly preferable that the resin composition contains azelaic acid, azelaic acid salt, glutaric acid or a glutaric acid salt, and glycerin or 1,3-propanediol in a state where azelaic acid, azelaic acid salt, glutaric acid or a glutaric acid salt is dissolved in glycerin or 1,3-propanediol. From the viewpoint of improving the coatability and screen printability of the resin composition, it is particularly preferable that the resin composition contains glutaric acid or a glutaric acid salt, and glycerin in a state where glutaric acid or a glutaric acid salt is dissolved in glycerin. From the viewpoint of improving the coatability and screen printability of the resin composition, it is particularly preferable that the resin composition contains glutaric acid and glycerin in a state where glutaric acid is dissolved in glycerin.

[0094] The hydrogen bond term δH in the Hansen solubility parameter of the thixotropic agent is preferably 10 MPa 1 / 2More preferably, 12MPa 1 / 2 More preferably, 14 MPa 1 / 2 More preferably, 16 MPa 1 / 2 or more. When the hydrogen bond term δH in the Hansen solubility parameter of the thixotropic agent is equal to or more than the lower limit, the coating property and screen printability of the resin composition can be improved. The upper limit of the hydrogen bond term δH in the Hansen solubility parameter of the thixotropic agent is not particularly limited. The hydrogen bond term δH in the Hansen solubility parameter of the thixotropic agent is 100 MPa 1 / 2 It may be less than 50MPa 1 / 2 It may be the following.

[0095] The hydrogen bond term ΔH in the Hansen solubility parameters of the thixotropic agent can be easily estimated, for example, by using computer software "Hansen Solubility Parameters in Practice (HSPiP)".

[0096] In 100% by weight of the resin composition, the content of the thixotropic agent is preferably 1% by weight or more, more preferably 2% by weight or more, and even more preferably 3% by weight or more, and is preferably 20% by weight or less, more preferably 15% by weight or less, and even more preferably 10% by weight or less. When the content of the thixotropic agent is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0097] In 100% by weight of the resin composition, the content of the glycerin is preferably 1% by weight or more, more preferably 2% by weight or more, and even more preferably 3% by weight or more, and is preferably 20% by weight or less, more preferably 15% by weight or less, and even more preferably 10% by weight or less. When the content of the glycerin is equal to or more than the lower limit and equal to or less than the upper limit, the coatability and screen printability of the resin composition can be improved.

[0098] (solder particles) The resin composition includes solder particles. The solder particles are formed of solder at both the center and the outer surface. The solder particles are particles in which both the center and the outer surface are solder. When conductive particles having a base particle formed of a material other than solder and a solder portion arranged on the surface of the base particle are used instead of the solder particles, the conductive particles are less likely to gather on the electrode. In addition, the conductive particles have low solder bonding between the conductive particles, so that the conductive particles that have moved onto the electrode tend to move out of the electrode.

[0099] The solder is preferably a metal (low melting point metal) having a melting point of 450°C or less. The solder particles are preferably metal particles (low melting point metal particles) having a melting point of 450°C or less. The low melting point metal particles are particles containing a low melting point metal. The low melting point metal refers to a metal having a melting point of 450°C or less. The melting point of the low melting point metal is preferably 300°C or less, more preferably 220°C or less, and even more preferably 190°C or less.

[0100] The melting point of the solder particles is preferably 100° C. or higher, more preferably 105° C. or higher, and preferably 250° C. or lower, more preferably 245° C. or lower. When the melting point of the solder particles is equal to or higher than the lower limit and equal to or lower than the upper limit, the cohesiveness of the solder during conductive connection can be more effectively improved. When the melting point of the solder particles is equal to or higher than the lower limit and equal to or lower than the upper limit, when electrodes are electrically connected, the conductivity reliability can be more effectively improved and the insulation reliability can be more effectively improved.

[0101] The melting point of the solder particles can be determined by differential scanning calorimetry (DSC), such as the "EXSTAR DSC7020" manufactured by SII Corporation.

[0102] The solder particles preferably contain 90% or more by weight of solder in 100% by weight of the solder particles. The solder particles also preferably contain tin. In 100% by weight of the metals contained in the solder particles, the tin content is preferably 30% or more by weight, more preferably 40% or more by weight, even more preferably 70% or more by weight, and particularly preferably 90% or more by weight. When the tin content in the solder particles is equal to or greater than the lower limit, the connection reliability between the solder portion and the electrode can be more effectively improved.

[0103] The tin content can be measured using a high-frequency inductively coupled plasma atomic emission spectrometer ("ICP-AES" manufactured by Horiba, Ltd.) or a fluorescent X-ray analyzer ("EDX-800HS" manufactured by Shimadzu Corporation).

[0104] By using the solder particles, the solder melts and bonds to the electrodes, and the solder portion conducts electricity between the electrodes. For example, the solder portion and the electrodes are easily in surface contact rather than point contact, so that the connection resistance is reduced. In addition, the use of the solder particles increases the bonding strength between the solder portion and the electrodes, so that the solder portion and the electrodes are less likely to peel off, and the reliability of the conduction and the reliability of the connection can be more effectively improved.

[0105] The low melting point metal constituting the solder particles is not particularly limited. The low melting point metal is preferably tin or an alloy containing tin. Examples of the alloy include a tin-silver alloy, a tin-copper alloy, a tin-silver-copper alloy, a tin-bismuth alloy, a tin-zinc alloy, and a tin-indium alloy. Since the low melting point metal has excellent wettability with respect to the electrode, it is preferable that the low melting point metal is tin, a tin-silver alloy, a tin-silver-copper alloy, a tin-bismuth alloy, or a tin-indium alloy. It is more preferable that the low melting point metal is a tin-bismuth alloy or a tin-indium alloy.

[0106] The solder particles are preferably a filler metal having a liquidus temperature of 450° C. or less based on JIS Z3001: Welding Terminology. Examples of the composition of the solder particles include metal compositions containing zinc, gold, silver, lead, copper, tin, bismuth, indium, etc. The solder particles preferably do not contain lead, and preferably contain tin and indium, or tin and bismuth.

[0107] In order to more effectively increase the bonding strength between the solder part and the electrode, the solder particles may contain metals such as nickel, copper, antimony, aluminum, zinc, iron, gold, titanium, phosphorus, germanium, tellurium, cobalt, bismuth, manganese, chromium, molybdenum, and palladium. In order to more effectively increase the bonding strength between the solder part and the electrode, the solder particles preferably contain nickel, copper, antimony, aluminum, or zinc. In order to more effectively increase the bonding strength between the solder part and the electrode, the content of these metals for increasing the bonding strength is preferably 0.0001% by weight or more, and preferably 1% by weight or less, based on 100% by weight of the metal contained in the solder particles.

[0108] The average particle diameter of the solder particles is preferably 0.01 μm or more, more preferably 0.03 μm or more. When the average particle diameter of the solder particles is equal to or more than the lower limit, the solder can be arranged on the electrode more efficiently. The average particle diameter of the solder particles may be 10 μm or less, 5 μm or less, or 3 μm or less. The range of the average particle diameter of the solder particles can be set by appropriately selecting the lower limit and the upper limit.

[0109] The average particle diameter of the solder particles is a number average particle diameter. The average particle diameter of the solder particles is obtained, for example, by observing 50 arbitrary solder particles with an electron microscope or an optical microscope and calculating the average particle diameter of each solder particle, or by performing laser diffraction type particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each solder particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary solder particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the laser diffraction type particle size distribution measurement, the particle diameter of each solder particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the solder particles is preferably calculated by laser diffraction type particle size distribution measurement.

[0110] The coefficient of variation (CV value) of the particle diameter of the solder particles is preferably 5% or more, more preferably 10% or more, and is preferably 40% or less, more preferably 30% or less. When the coefficient of variation of the particle diameter of the solder particles is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be arranged on the electrode more efficiently. However, the CV value of the particle diameter of the solder particles may be less than 5%.

[0111] The coefficient of variation (CV value) can be measured as follows.

[0112] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of solder particle diameter Dn: Average particle size of solder particles

[0113] The shape of the solder particles is not particularly limited, and may be spherical, may be a shape other than spherical, or may be flat.

[0114] In 100% by weight of the resin composition, the content of the solder particles is preferably 1% by weight or more, more preferably 2% by weight or more, even more preferably 10% by weight or more, particularly preferably 20% by weight or more, most preferably 30% by weight or more, and preferably 80% by weight or less, more preferably 60% by weight or less, and even more preferably 50% by weight or less. When the content of the solder particles is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be arranged on the electrodes more efficiently, it is easy to arrange a large amount of solder between the electrodes, and the electrical reliability can be improved more effectively. From the viewpoint of improving the electrical reliability more effectively, the content of the solder particles is preferably large.

[0115] (Other ingredients) The resin composition may contain various additives, as necessary, such as a filler, an extender, a softener, a plasticizer, a thickener, a leveling agent, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.

[0116] (Connection structure and method for manufacturing the connection structure) The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection part connecting the first connection target member and the second connection target member. In the connection structure according to the present invention, the material of the connection part is the above-mentioned resin composition. In the connection structure according to the present invention, the first electrode and the second electrode are electrically connected by a solder part in the connection part.

[0117] In the connection structure according to the present invention, a specific resin composition is used, so that the solder is easily collected between the first electrode and the second electrode, and the solder can be efficiently arranged on the electrodes (lines). In addition, a part of the solder is unlikely to be arranged in an area (space) where no electrodes are formed, and the amount of solder arranged in the area where no electrodes are formed can be significantly reduced. Therefore, the reliability of the conduction between the first electrode and the second electrode can be improved. Moreover, it is possible to prevent electrical connection between laterally adjacent electrodes that should not be connected, and to improve the reliability of insulation.

[0118] In addition, in order to efficiently place the solder on the electrodes and significantly reduce the amount of solder placed in areas where no electrodes are formed, it is preferable to use a conductive paste rather than a conductive film as the resin composition.

[0119] In the connection structure, it is preferable that the first connection target member is a circuit board, and the second connection target member is a semiconductor chip.

[0120] The method for producing a connection structure according to the present invention comprises the following steps: (1) a first arrangement step of using the above-mentioned resin composition to arrange the resin composition on a surface of a first connection target member having at least one first electrode on its surface; (2) a second arrangement step of moving a second connection target member having at least one second electrode on its surface onto a surface of the resin composition opposite the first connection target member side by a laser transfer method, and arranging the second connection target member so that the first electrode and the second electrode face each other; and (3) a connection step of forming a connection part connecting the first connection target member and the second connection target member from the resin composition by heating the resin composition to a temperature equal to or higher than the melting point of the solder particles, and electrically connecting the first electrode and the second electrode by a solder part in the connection part.

[0121] Since the method for manufacturing a connection structure according to the present invention has the above-mentioned configuration, it is possible to improve the capture of the second connection target component (semiconductor chip) that arrives at high speed by the laser transfer method.

[0122] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings.

[0123] FIG. 1 is a cross-sectional view that typically shows a connection structure obtained by using a resin composition according to one embodiment of the present invention.

[0124] 1 includes a first connection target member 2, a second connection target member 3, and a connection part 4 connecting the first connection target member 2 and the second connection target member 3. The connection part 4 is formed from the above-mentioned resin composition.

[0125] In this embodiment, the resin composition includes a thermosetting component, a flux, a thixotropic agent that is liquid at 25° C., and solder particles. In this embodiment, a conductive paste is used as the resin composition.

[0126] The connection portion 4 has a solder portion 4A in which a plurality of solder particles are gathered and joined together, and a cured portion 4B in which a thermosetting component is thermally cured.

[0127] The first connection target member 2 has a plurality of first electrodes 2a on its surface (upper surface). The second connection target member 3 has a plurality of second electrodes 3a on its surface (lower surface). The first electrode 2a and the second electrode 3a are electrically connected by the solder portion 4A. Therefore, the first connection target member 2 and the second connection target member 3 are electrically connected by the solder portion 4A. In the connection portion 4, solder is not present in a region (hardened portion 4B) other than the solder portion 4A gathered between the first electrode 2a and the second electrode 3a. In a region (hardened portion 4B) other than the solder portion 4A, solder is not present apart from the solder portion 4A. In addition, if the amount is small, solder may be present in a region (hardened portion 4B) other than the solder portion 4A gathered between the first electrode 2a and the second electrode 3a.

[0128] As shown in FIG. 1, in the connection structure 1, a plurality of solder particles are gathered between the first electrode 2a and the second electrode 3a, and after the plurality of solder particles melt, the molten solder particles wet and spread over the surface of the electrode, and then solidify to form the solder portion 4A. Therefore, the connection area between the solder portion 4A and the first electrode 2a, and between the solder portion 4A and the second electrode 3a is increased. That is, by using the solder particles, the contact area between the solder portion 4A and the first electrode 2a, and between the solder portion 4A and the second electrode 3a is increased compared to the case where the outer surface portion of the conductive portion is made of a metal such as nickel, gold, or copper. Therefore, the conduction reliability and connection reliability of the connection structure 1 are increased. In addition, the flux and thixotropic agent contained in the resin composition are generally gradually deactivated by heating.

[0129] In the connection structure 1 shown in FIG. 1, all of the solder portion 4A is located in the opposing region between the first and second electrodes 2a, 3a. The connection structure 1X of the modified example shown in FIG. 5 differs from the connection structure 1 shown in FIG. 1 only in the connection portion 4X. The connection portion 4X has a solder portion 4XA and a hardened portion 4XB. Like the connection structure 1X, most of the solder portion 4XA is located in the opposing region of the first and second electrodes 2a, 3a, and a part of the solder portion 4XA may protrude laterally from the opposing region of the first and second electrodes 2a, 3a. The solder portion 4XA protruding laterally from the opposing region of the first and second electrodes 2a, 3a is a part of the solder portion 4XA, and is not solder separated from the solder portion 4XA. In this embodiment, the amount of solder separated from the solder portion can be reduced, but the solder separated from the solder portion may be present in the hardened portion.

[0130] If the amount of solder particles used is reduced, it becomes easier to obtain the connection structure 1. If the amount of solder particles used is increased, it becomes easier to obtain the connection structure 1X.

[0131] The thickness of the solder portion between the first electrode and the second electrode is preferably 10 μm or more, more preferably 20 μm or more, and preferably 100 μm or less, more preferably 80 μm or less. In the first electrode and the second electrode, the solder wetted area on the surface of the electrode (the area in contact with the solder in 100% of the exposed area of ​​the electrode) is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, and preferably 100% or less. When the solder portion in the connection satisfies the above-mentioned preferable aspects, the electrical continuity reliability and the insulation reliability can be further effectively improved.

[0132] In the connection structure 1, 1X, when the opposing portion of the first electrode 2a and the second electrode 3a is viewed in the stacking direction of the first electrode 2a, the connection portion 4, 4X, and the second electrode 3a, it is preferable that the solder portion 4A, 4XA in the connection portion 4, 4X is disposed in 50% or more of the 100% area of ​​the opposing portion of the first electrode 2a and the second electrode 3a. When the solder portion 4A, 4XA in the connection portion 4, 4X satisfies the above-mentioned preferable aspect, the electrical connection reliability can be further improved.

[0133] When the portion where the first electrode and the second electrode face each other is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode, the solder portion in the connection portion is preferably arranged in 50% or more of the 100% area of ​​the portion where the first electrode and the second electrode face each other. When the portion where the first electrode and the second electrode face each other is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode, the solder portion in the connection portion is more preferably arranged in 60% or more of the 100% area of ​​the portion where the first electrode and the second electrode face each other. When the portion where the first electrode and the second electrode face each other is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode, the solder portion in the connection portion is further preferably arranged in 70% or more of the 100% area of ​​the portion where the first electrode and the second electrode face each other. It is particularly preferable that the solder portion in the connection portion is disposed in 80% or more of the 100% area of ​​the facing portion of the first electrode and the second electrode when the facing portion of the first electrode and the second electrode is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode. It is most preferable that the solder portion in the connection portion is disposed in 90% or more of the 100% area of ​​the facing portion of the first electrode and the second electrode when the facing portion of the first electrode and the second electrode is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode. When the solder portion in the connection portion satisfies the above-mentioned preferable aspects, the electrical connection reliability can be further improved.

[0134] When the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection portion, and the second electrode, it is preferable that 60% or more of the solder portion in the connection portion is disposed in the portion where the first electrode and the second electrode face each other. It is more preferable that 70% or more of the solder portion in the connection portion is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection portion, and the second electrode. It is even more preferable that 90% or more of the solder portion in the connection portion is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection portion, and the second electrode. It is particularly preferable that 95% or more of the solder in the connection part is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection part, and the second electrode. It is most preferable that 99% or more of the solder in the connection part is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection part, and the second electrode. When the solder in the connection part satisfies the above-mentioned preferable aspect, the electrical connection reliability can be further improved.

[0135] Next, an example of a method for producing a connection structure 1 using a resin composition according to one embodiment of the present invention will be described with reference to Figures 2 to 4. Figures 2 to 4 are cross-sectional views for explaining each step of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention.

[0136] First, a first connection target member (circuit board) 2 having a first electrode 2a on its surface (upper surface) is prepared. Next, as shown in Fig. 2, a resin composition 11 containing a thermosetting component 11B, solder particles 11A, flux 11C, and a thixotropic agent (not shown) that is liquid at 25°C is placed on the surface of the first connection target member (circuit board) 2 (first placing step). The thermosetting component 11B contains a thermosetting compound.

[0137] A resin composition 11 is placed on the surface of the first connection target member (circuit board) 2 on which the first electrode 2a is provided. After placing the resin composition 11, the solder particles 11A, the flux 11C, and the thixotropic agent are placed on both the first electrode 2a (lines) and the area (space) where the first electrode 2a is not formed. The resin composition may be placed only on the surface of the first electrode.

[0138] There is no particular limitation on the method for disposing the resin composition 11. Examples of the method for disposing the resin composition 11 include application by a dispenser, screen printing, and ejection by an inkjet device.

[0139] Also, a second connection target member (semiconductor chip) 3 having a second electrode 3a on its surface (lower surface) is prepared. The second connection target member (semiconductor chip) 3 having the second electrode 3a on its surface (lower surface) is disposed on the surface of the support film 6 side of the transfer source substrate including a support member 5 and a support film 6. The second connection target member (semiconductor chip) 3 having the second electrode 3a on its surface (lower surface) is disposed on the surface of the support film 6.

[0140] Next, as shown in FIG. 3, in the resin composition 11 on the surface of the first connection target member (circuit board) 2, the second connection target member (semiconductor chip) 3 is moved by a laser transfer method onto the surface of the resin composition 11 opposite to the first connection target member (circuit board) 2 side, and the second connection target member (semiconductor chip) 3 is placed (second placement step). The second connection target member (semiconductor chip) 3 is placed on the surface of the resin composition 11 from the second electrode 3a side. In the second placement step, a laser is irradiated from the support member 5 side of the transfer source substrate by the laser irradiation device 51, so that the curing reaction of the curable component (resin component) in the support film 6 progresses, and the adhesive force of the surface of the support film 6 is greatly reduced. As a result, the second connection target member (semiconductor chip) 3 is peeled off from the transfer source substrate (particularly, the support film 6) and moved onto the surface of the resin composition 11 opposite to the first connection target member (circuit board) 2 side. The second connection target member (semiconductor chip) 3 moves by itself, for example, in a state where the surface of the second connection target member (semiconductor chip) 3 is not in contact with other members (is not held by other members). At this time, the first electrode 2a and the second electrode 3a face each other.

[0141] In this embodiment, since the resin composition is used, the second connection target member (semiconductor chip) 3 flying at high speed by the laser transfer method can be captured more easily in the second placement step. As a result, the flying second connection target member (semiconductor chip) can be accurately placed at a predetermined location on the first connection target member (circuit board) (effectively suppressing misalignment during placement of the semiconductor chip).

[0142] Next, the resin composition 11 is heated to a temperature equal to or higher than the melting point of the solder particles 11A. Preferably, the resin composition 11 is heated to a temperature equal to or higher than the curing temperature of the thermosetting component 11B (thermosetting compound). During this heating, the solder particles 11A that existed in the region where no electrode is formed gather between the first electrode 2a and the second electrode 3a (self-aggregation effect). When a conductive paste is used instead of a conductive film, the solder particles 11A gather more effectively between the first electrode 2a and the second electrode 3a. In addition, the solder particles 11A melt and bond to each other. In addition, the thermosetting component 11B is thermally cured. As a result, as shown in FIG. 4, a connection portion 4 that connects the first connection target member (circuit board) 2 and the second connection target member (semiconductor chip) 3 is formed by the resin composition 11. The connection part 4 is formed by the resin composition 11, the solder part 4A is formed by bonding the multiple solder particles 11A, the thermosetting component 11B is thermally cured to form the hardened part 4B, and the first electrode 2a and the second electrode 3a are electrically connected by the solder part 4A in the connection part 4 (connection step). If the solder particles 11A move sufficiently, it is not necessary to keep the temperature constant from the start of the movement of the solder particles 11A that are not located between the first electrode 2a and the second electrode 3a until the movement of the solder particles 11A between the first electrode 2a and the second electrode 3a is completed.

[0143] It is preferable not to apply pressure in the second arrangement step and the connection step. In this case, the weight of the second connection target member (semiconductor chip) 3 is added to the resin composition 11. Therefore, when the connection part 4 is formed, the solder particles 11A gather more effectively between the first electrode 2a and the second electrode 3a. If pressure is applied in at least one of the second arrangement step and the connection step, the action of the solder particles 11A to gather between the first electrode 2a and the second electrode 3a tends to be inhibited.

[0144] In addition, since no pressure is applied in this embodiment, even if the first connection target member (circuit board) 2 and the second connection target member (semiconductor chip) 3 are superimposed with the first electrode 2a and the second electrode 3a slightly misaligned, the first electrode 2a and the second electrode 3a can be connected by correcting the slight misalignment (self-alignment effect). This is because the molten solder self-aggregating between the first electrode 2a and the second electrode 3a is energetically more stable when the contact area between the solder between the first electrode 2a and the second electrode 3a and the other components of the resin composition is minimized, and a force acts to make the connection structure with the minimum area, which is an aligned connection structure. At this time, it is desirable that the resin composition is not cured, and that the viscosity of the components of the resin composition other than the solder particles is sufficiently low at that temperature and time.

[0145] In this manner, the connection structure 1 shown in FIG. 1 is obtained. The second arrangement step and the connection step may be performed consecutively. After the second arrangement step, the resulting laminate of the first connection target member 2, the resin composition 11, and the second connection target member 3 may be moved to a heating section to perform the connection step. To perform the heating, the laminate may be placed on a heating member, or the laminate may be placed in a heated space.

[0146] In the second arrangement step, it is preferable to move the second connection target member on the surface of the resin composition opposite to the first connection target member side by a laser transfer method at a speed of 1 cm / s or more, and arrange the second connection target member so that the first electrode and the second electrode face each other. In the second arrangement step, the speed at which the second connection target member is moved by the laser transfer method on the surface of the resin composition opposite to the first connection target member side is preferably 5 cm / s or more, more preferably 10 cm / s or more, and even more preferably 50 cm / s or more. The upper limit of the speed at which the second connection target member is moved by the laser transfer method is not particularly limited. In the laser transfer method in the second arrangement step, the second connection target member may be moved on the surface of the resin composition opposite to the first connection target member side at a speed of 500 cm / s or less. In the second placement step, the range of the speed at which the second connection target component is moved by a laser transfer method onto the surface of the resin composition opposite the first connection target component side can be set by appropriately selecting the lower limit value and the upper limit value.

[0147] The heating temperature in the connecting step is preferably 250° C. or more, more preferably 300° C. or more, and preferably 450° C. or less, more preferably 400° C. or less, and even more preferably 350° C. or less. When the heating temperature in the connecting step is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be more efficiently disposed on the electrodes, and the reliability of conductivity between the upper and lower electrodes to be connected can be more effectively improved.

[0148] Heating methods for the above-mentioned connection process include a method of heating the entire connection structure using a reflow furnace or oven to a temperature above the melting point of the solder and above the curing temperature of the thermosetting component, and a method of locally heating only the connection portion of the connection structure.

[0149] Examples of tools used in the localized heating method include a hot plate, a heat gun that applies hot air, a soldering iron, and an infrared heater.

[0150] In addition, when applying localized heating with a hot plate, it is preferable to form the upper surface of the hot plate from a metal with high thermal conductivity directly below the connection portion, and from a material with low thermal conductivity such as a fluororesin for other areas where it is not desirable to heat the connection portion.

[0151] The first and second connection target members are not particularly limited. Examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The semiconductor chip may be an LED chip, and the semiconductor package may be an LED package. The second connection target member is preferably an electronic component. The second connection target member is preferably a semiconductor chip, more preferably an LED chip, and even more preferably a micro LED chip.

[0152] At least one of the first connection target member and the second connection target member is preferably a resin film, a flexible printed circuit board, a flexible flat cable, or a rigid flexible substrate. The first connection target member is preferably a resin film, a flexible printed circuit board, a flexible flat cable, or a rigid flexible substrate. Resin films, flexible printed circuit boards, flexible flat cables, and rigid flexible substrates have the properties of being highly flexible and relatively lightweight. When a conductive film is used to connect such connection target members, solder tends not to gather on the electrodes. In contrast, by using a conductive paste, even if a resin film, a flexible printed circuit board, a flexible flat cable, or a rigid flexible substrate is used, solder can be efficiently gathered on the electrodes, thereby sufficiently increasing the reliability of conduction between the electrodes.

[0153] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.

[0154] The support member is not particularly limited, and examples of the support member include a glass substrate, a sapphire substrate, a silicone substrate, a metal substrate, and an organic substrate.

[0155] The support film is not particularly limited. Examples of the support film include a silicone resin film, an acrylic resin film, and a polyimide resin film. The support film preferably has an adhesive layer.

[0156] In the second disposing step, the integrated light amount of the irradiated laser is preferably 100 mJ / cm 2 More preferably, 150 mJ / cm 2 More preferably, 200 mJ / cm 2 or more, preferably 400 mJ / cm 2 Less than or equal to 350 mJ / cm 2 Less than 300 mJ / cm, more preferably 300 mJ / cm 2 When the integrated light amount of the laser irradiated in the second placing step is equal to or more than the lower limit and equal to or less than the upper limit, the ability to capture semiconductor chips flying at high speed can be further improved.

[0157] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0158] Thermosetting component (thermosetting compound): Phenol novolac type epoxy compound ("JER152" manufactured by Mitsubishi Chemical Corporation) Bisphenol F type epoxy compound (DIC "830-S")

[0159] Flux: Benzylamine adipate (first flux (main chain carbon number 4), average particle size 10 μm, melting point 180° C., prepared according to Synthesis Example 1 below) Glutaric acid benzylamine salt (second flux (main chain carbon number 3), average particle size 10 μm, melting point 108° C., prepared according to Synthesis Example 2 below) Azelaic acid stearylamine salt (second flux (main chain carbon number 7), average particle size 10 μm, melting point 110° C., prepared according to Synthesis Example 3 below)

[0160] Synthesis example 1: In a glass bottle, 24 g of water as a reaction solvent and 14.612 g of adipic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed and heated at 100°C for 10 minutes to dissolve. Then, 10.715 g of benzylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed and stirred for about 5 minutes to obtain a mixed solution. The obtained mixed solution was placed in a refrigerator at 5°C to 10°C and left overnight. The precipitated crystals were separated by filtration, washed with water, and vacuum dried to obtain benzylamine adipate salt (average particle size 30 μm). The obtained benzylamine adipate salt was pulverized by a jet mill pulverization method to obtain benzylamine adipate salt with an average particle size of 10 μm.

[0161] Synthesis example 2: In a glass bottle, 24 g of water as a reaction solvent and 13.212 g of glutaric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed and dissolved at room temperature until homogenous. Then, 10.715 g of benzylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed and stirred for about 5 minutes to obtain a mixed solution. The obtained mixed solution was placed in a refrigerator at 5°C to 10°C and left overnight. The precipitated crystals were separated by filtration, washed with water, and vacuum dried to obtain benzylamine glutarate. The obtained benzylamine glutarate was pulverized by a jet mill pulverization method to obtain benzylamine glutarate with an average particle size of 10 μm.

[0162] Synthesis example 3: In a glass bottle, 24 g of water as a reaction solvent and 9.411 g of azelaic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed and heated at 100°C for 10 minutes to dissolve. Then, 13.476 g of stearylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed and stirred for about 5 minutes to obtain a mixed solution. The resulting mixed solution was placed in a refrigerator at 5°C to 10°C and left overnight. The precipitated crystals were separated by filtration, washed with water, and vacuum dried to obtain azelaic acid stearylamine salt (average particle size 30 μm). The obtained azelaic acid stearylamine salt was pulverized by a jet mill pulverization method to obtain adipic acid benzylamine salt with an average particle size of 10 μm.

[0163] Thixotropic agent with dissolved flux: A thixotropic agent in which glutaric acid is dissolved in glycerin (Nacalai Tesque's "Glycerol"; 30% by weight of glutaric acid and 70% by weight of glycerin; the hydrogen bond term in the Hansen solubility parameter of glycerin, δH, is 14.3 MPa) 1 / 2 )

[0164] Thixotropic Agent: Ethylene glycol (Wako Co., Ltd., liquid at 25°C, hydrogen bond term in Hansen solubility parameters δH 12.7MPa) 1 / 2 ) 1,3-propanediol (TCI, liquid at 25°C, hydrogen bond term in Hansen solubility parameters δH 12.9MPa) 1 / 2 )

[0165] Solder particles: SnAgCu solder particles (melting point 220℃, solder particles selected from Mitsui Mining & Smelting Co., Ltd.'s "Sn96.5Ag3Cu0.5", average particle diameter 3μm) SnBi solder particles (melting point 139℃, solder particles selected from "Sn42Bi58" manufactured by Mitsui Mining & Smelting Co., Ltd., average particle diameter 3μm)

[0166] (Average particle size of flux and solder particles) The average particle diameters of the flux and solder particles were measured using a laser diffraction particle size distribution measuring device ("LA-920" manufactured by Horiba, Ltd.).

[0167] (Melting point of solder particles and flux) The melting points of the solder particles and the flux were calculated using differential scanning calorimetry (DSC), using an "EXSTAR DSC7020" manufactured by SII Corporation.

[0168] Example 4,6~8, Reference example 1~3,5 and Comparative Examples 1-2) (1) Preparation of resin composition (anisotropic conductive paste) The components shown in Tables 1 to 3 below were mixed in the amounts shown in Tables 1 to 3 below to obtain resin compositions (anisotropic conductive pastes).

[0169] (2) Fabrication of connection structure As the first connection target component (circuit board), a glass substrate (thickness: 0.7 mm) having multiple electrodes (first electrode, copper electrode 23 μm wide × 30 μm long × 12 μm thick, 14 μm space between electrodes) on its surface was prepared.

[0170] As the second connection target component (semiconductor chip), a micro LED chip (material: GaN, thickness: 0.01 mm) having multiple electrodes (second electrode, gold electrode measuring 20 μm wide x 20 μm long x 3 μm thick, with a space between electrodes of 10 μm) on its surface was prepared.

[0171] The resin composition (anisotropic conductive paste) immediately after preparation was applied to the upper surface of the glass substrate by screen printing to a thickness of 10 μm to form a resin composition (anisotropic conductive paste) layer. Next, a semiconductor chip was laminated on the upper surface of the resin composition (anisotropic conductive paste) layer by a laser transfer method so that the electrodes faced each other. From that state, the resin composition (anisotropic conductive paste) layer was heated so that the temperature of the resin composition (anisotropic conductive paste) layer reached the melting point of the solder particles 5 seconds after the start of the temperature rise. Furthermore, the resin composition (anisotropic conductive paste) layer was heated so that the temperature of the resin composition (anisotropic conductive paste) layer reached 250° C. 10 seconds after the start of the temperature rise, and the resin composition (anisotropic conductive paste) layer was cured to obtain a connection structure. No pressure was applied during heating.

[0172] (evaluation) (1) Contact angle with water at 25°C For the resulting resin composition, the contact angle with water at 25° C. was measured by the method described above.

[0173] (2) Screen printability (coating ability) The obtained resin composition (anisotropic conductive paste) was screen printed on a glass substrate using a metal mask with an opening of 114 μm×60 μm and a thickness of 10 μm. The printed surface of 50 printed patterns was observed with a laser microscope immediately after printing to calculate the volume of the resin composition applied to the glass substrate, and the ratio X (%) of the volume of the resin composition applied to the glass substrate to the volume of each opening of the metal mask was calculated. The screen printability was evaluated according to the following criteria.

[0174] [Criteria for Screen Printability] ○○: The percentage of X is 50% or more ○: Proportion X is 40% or more but less than 50% △: Proportion X is 30% or more but less than 40% ×: Proportion X is less than 30%

[0175] (3) Solder cohesion In the resulting connection structures (20 pieces), when the portion where the first electrode and the second electrode face each other in the lamination direction of the first electrode, the connection portion, and the second electrode is viewed, the ratio of the area where the solder portion in the connection portion is arranged to the 100% area of ​​the portion where the first electrode and the second electrode face each other was evaluated. The values ​​for the 20 pieces were averaged to find the area ratio Y. From the area ratio Y, the cohesion of the solder during conductive connection was evaluated according to the following criteria.

[0176] [Criteria for determining solder cohesion] ○○: Proportion Y is 70% or more ○: Proportion Y is 60% or more but less than 70% △: Proportion Y is 50% or more but less than 60% ×: Proportion Y is less than 50%

[0177] (4) Captivity of semiconductor chips In "(2) Screen printability", a semiconductor chip was moved by laser transfer at a speed of 1 cm / s on the surface opposite the glass substrate of the resin composition applied by screen printing onto the glass substrate, and 20 semiconductor chips were arranged so that the first electrode of the glass substrate and the second electrode of the semiconductor chip faced each other. Of the 20 semiconductor chips, the percentage Z of the number of semiconductor chips captured at a position within ±3 μm of a predetermined position was calculated. The captureability of the semiconductor chips was evaluated according to the following criteria.

[0178] [Criteria for determining the capture of semiconductor chips] ○○: Proportion Z is 70% or more ○: Proportion Z is 50% or more but less than 70% ×: Proportion Z is less than 50%

[0179] The results are shown in Tables 1 to 3 below.

[0180] [Table 1]

[0181] [Table 2]

[0182] [Table 3] [Explanation of symbols]

[0183] 1,1X…Connection structure 2...First connection target member (circuit board) 2a...First electrode 3...Second connection target component (semiconductor chip) 3a...Second electrode 4,4X…Connection part 4A, 4XA...Solder part 4B,4XB…Cured product part 5...Support member (original substrate) 6...Support film (original substrate) 11...Resin composition 11A…Solder particles 11B...Thermosetting component 11C…Flux 51...Laser irradiation device

Claims

1. The adhesive includes a thermosetting component, a flux, a thixotropic agent that is liquid at 25° C., and solder particles; the flux includes a first flux having an even number of carbon atoms in its main chain and a second flux having an odd number of carbon atoms in its main chain; A resin composition, wherein the content of the second flux is 1% by weight or more and 20% by weight or less based on 100% by weight of the resin composition.

2. The hydrogen bond term δH in the Hansen solubility parameter of the thixotropic agent is 10 MPa 1/2 That's all. the number of carbon atoms in the main chain of the first flux is an even number of 4 to 14, The resin composition according to claim 1 , wherein the number of carbon atoms in the main chain of the second flux is an odd number of 3 to 11.

3. The resin composition according to claim 1 or 2, wherein the first flux has an average particle size of 10 μm or less.

4. The resin composition according to claim 1 or 2, wherein the second flux is soluble in the thixotropic agent at 25°C.

5. The resin composition according to claim 1 or 2, wherein the thixotropic agent comprises glycerin.

6. The resin composition according to claim 1 or 2, wherein the content of the flux is 5% by weight or more and 25% by weight or less based on 100% by weight of the resin composition.

7. The resin composition according to claim 1 or 2, wherein the solder particles have an average particle size of 10 μm or less.

8. A first arrangement step of arranging the resin composition on a surface of a first connection target member having at least one first electrode on a surface thereof, using the resin composition according to claim 1 or 2; A second arrangement step of moving a second connection target member having at least one second electrode on a surface thereof by a laser transfer method onto a surface of the resin composition opposite to the first connection target member side, and arranging the second connection target member so that the first electrode and the second electrode face each other; A method for manufacturing a connection structure, comprising: a connection process in which a connection portion connecting the first connection target member and the second connection target member is formed from the resin composition by heating the resin composition to a temperature equal to or higher than the melting point of the solder particles, and the first electrode and the second electrode are electrically connected by a solder portion in the connection portion.

9. 9. The method for manufacturing a connection structure described in claim 8, wherein in the second placement step, the second connection target member is moved at a speed of 1 cm / s or more by a laser transfer method onto the surface of the resin composition opposite the first connection target member, and the second connection target member is placed so that the first electrode and the second electrode face each other.

Citation Information

Patent Citations

  • Filter device

    JP1990500962A

  • Treatment of drug-resistant organisms

    JP2004508337A

  • Conductive material, connection structure and production method of connection structure

    JP2019096550A

  • Preliminarily cured product, roughened preliminarily cured product, and laminate

    WO2012131971A1

  • Conductive material and connection structure

    WO2017130892A1